Haptics. perception, devices, control, and applications : 10th International Conference, EuroHaptics 2016, London, UK, July 4-7, 2016, Proceedings /: perception, devices, control, and applications : 10th International Conference, EuroHaptics 2016, London, UK, July 4-7, 2016, Proceedings. Part II : (2016) - Unknown
No abstract available